Perbedaan Homesickness Mahasiswa Rantau Tahun Pertama antara Laki-Laki dan Perempuan di Universitas Negeri Padang - Geni Novella (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
The aim of this study is to examine the differences in levels of homesickness between male and female first-year students who are away from home at Universitas Negeri Padang. This research uses a quantitative method with a comparative research design. The research population includes all active students from the 2024 cohort who are from outside the city and live far from their immediate family while pursuing their studies. The sample was determined using purposive sampling, with a total of 200 students, consisting of 100 male and 100 female students. Data was collected using a homesickness scale questionnaire developed by Archer (1998) and constructed by Sinantia et al. (2024). The results of the study reveal a significant difference in homesickness levels between male and female students, with a significance value of 0.000 (< 0.05). The score distribution shows that the majority of female students fall into the high category (51%), while the majority of male students fall into the moderate category (58%).